Analisis Faktor Penyebab Ketidaklengkapan Rekam Medis Rawat Inap Puskesmas Kotakulon Tahun 2022 - Tiara Wirdathul Jannah; Selvia Juwita Swari; Gamasiano Alfiansyah; Maya Weka Santi (Indonesian Journal Publisher, 2024)
The provided information outlines a situation at the Kotakulon Health Center where inpatient medical record files are incomplete, failing to meet the standards for medical record filing completeness. The highest percentage of incompleteness was identified in several specific areas, including Pharmaceutical Care Forms, Drug Record Cards, Informed Consent, Entry and Exit Summary, and Discharge Planning, with an 87% incompleteness rate. To address this issue, a study was conducted to analyze the factors contributing to incomplete medical records for inpatients at the health center. The study results identified several factors contributing to incomplete medical records, including a lack of training, low self-awareness, poor discipline, insufficient communication, and the absence of a reward system. To address these issues, the proposed solution involved conducting outreach, training, and seminars, particularly within the inpatient unit, and encouraging officers to adhere to their standard operating procedures (SOPs) more diligently. This approach aims to improve medical record completeness and enhance the overall performance of the officers.